2018
DOI: 10.1038/s41598-017-18867-w
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stromal Cell-Derived Extracellular Vesicles Modify Microglial Response and Improve Clinical Outcomes in Experimental Spinal Cord Injury

Abstract: No current clinical intervention can alter the course of acute spinal cord injury (SCI), or appreciably improve neurological outcome. Mesenchymal stromal cells (MSCs) have been shown to modulate the injury sequelae of SCI largely via paracrine effects, although the mechanisms remain incompletely understood. One potential modality is through secretion of extracellular vesicles (EVs). In this study, we investigate whether systemic administration of EVs isolated from human MSCs (MSCEv) has the potential to be eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 69 publications
6
79
0
Order By: Relevance
“…Additionally, MSC transplantation can reduce the levels of proinflammatory cytokines, such as TNF-α and IL-1 [11,47], and inhibit NFκB signaling [12,48,49]. Moreover, MSCs are capable of switching microglia from a proinflammatory M1 phenotype towards an anti-inflammatory M2 phenotype in vitro [13] and in SCI models [50]. Furthermore, MSCs inhibit reactive astrogliosis in inflammationinduced preterm brain injury [51], attenuate GFAP overexpression in astrocytes in stroke [52], and modulate astrocytic end-feet in lipopolysaccharide-treated rats [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, MSC transplantation can reduce the levels of proinflammatory cytokines, such as TNF-α and IL-1 [11,47], and inhibit NFκB signaling [12,48,49]. Moreover, MSCs are capable of switching microglia from a proinflammatory M1 phenotype towards an anti-inflammatory M2 phenotype in vitro [13] and in SCI models [50]. Furthermore, MSCs inhibit reactive astrogliosis in inflammationinduced preterm brain injury [51], attenuate GFAP overexpression in astrocytes in stroke [52], and modulate astrocytic end-feet in lipopolysaccharide-treated rats [53].…”
Section: Discussionmentioning
confidence: 99%
“…Activated microglia/macrophages and immune cells at the lesion site after SCI can produce a series of proinflammatory cytokines, including TNF-α, IL-1 and IL-6 [88,89] that may lead to the activation of astroglial NFκB. Given that both MSCs and MSC-exo have been confirmed to inhibit proinflammatory microglia in SCI [50], it is possible that MSCs and MSC-exo exert effects on A1 astrocytes not only in a direct way but also mediated by a variety of inflammatory cells.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
“…MSCs, indirectly co‐cultured with microglia in vitro , directly counteract the pro‐inflammatory response of cells activated with inflammatory cytokines and induce persistent pro‐regenerative traits (Giunti et al, ; Zanier et al, ). More recent studies demonstrated that MSCs‐derived EVs may be sufficient to significantly dampen microglia response and improve functional recovery upon intravenous administration in traumatic brain or spinal cord injuries (L. X. Zhang, Yin, Zhang, & Deng, ; J. W. Kim, Ha, Molon, & Kim, ; Ruppert et al, ) as well as in a mouse model of AD. Despite these findings offer a hopeful opportunity to advance novel cell‐free therapeutic strategies that might prevail over the risks associated with the use of cells, a still unresolved issue is the molecular mechanism whereby the infused EVs reduce inflammation and rescue cognitive impairments in rodent models of neuroinflammatory diseases.…”
Section: An Attractive Cell Therapy Approach To Redirect Microglia Tomentioning
confidence: 99%
“…Zhang, Yin, Zhang, & Deng, 2015;J. W. Kim, Ha, Molon, & Kim, 2013;Ruppert et al, 2018) as well as in a mouse model of AD. Despite these findings offer a hopeful opportunity to advance novel cell-free therapeutic strategies that might prevail over the risks associated with the use of cells, a still unresolved issue is the molecular mechanism whereby the infused EVs reduce inflammation and rescue cognitive impairments in rodent models of neuroinflammatory diseases.…”
Section: Mir200b Reduces Inos Expression and No Production And Limitsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study exploring the role of BRD4 in inflammatory response regulation after SCI and describing a BRD4 inhibitor capable of suppressing inflammatory response via negatively modulating NF-κB and MAPK signalling pathways (Figure 8).BET family such as BRD4 are reported to activate many inflammation-related genes,26 and inflammation blocks functional recovery and aggravates neuropathic paresthesia in damaged spinal cord 27,28. To the best of our knowledge, this is the first study exploring the role of BRD4 in inflammatory response regulation after SCI and describing a BRD4 inhibitor capable of suppressing inflammatory response via negatively modulating NF-κB and MAPK signalling pathways (Figure 8).BET family such as BRD4 are reported to activate many inflammation-related genes,26 and inflammation blocks functional recovery and aggravates neuropathic paresthesia in damaged spinal cord 27,28.…”
mentioning
confidence: 99%